Model and Pattern Contextualization Domestic Violence - Ahmad Mukri Aji (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract:Domestic violence is a phenomenon that often occurs in any part of the world. The biggest victims are women who are wives, children and parents in the category of second-level victims. Any religion forbids a person to commit violence against fellow humans, especially against someone who should be protected. This study elaboratively wants to examine how models and patterns of violence in households are contextually. In addition to being examined the obligations of the government in finding solutions to solutions, both legal solutions and other alternative solutions.Keywords: Model, Pattern, Violence Abstrak:Kekerasan dalam rumah tangga merupakan fenomena yang masih kerap terjadi di belahan dunia manapun. Korban terbesar adalah wanita yang berstatus sebagai istri, sedang anak-anak dan orang tua dalam katagori korban level kedua. Agama manapun melarang seseorang melakukan kekerasaan terhadap sesama manusia, apalagi terhadap seseorang yang seharusnya dilindungi. Kajian ini secara elaboratif ingin mengkaji model dan pola kekerasaan dalam rumah tangga secara kontekstual. Selain juga dikaji kewajiban pemerintah dalam mencari solusi penyelesaiannya, baik solusi hukum maupun solusi alternatif lainnya. Kata Kunci: Model, Pola, Kekerasan